Permeability evolution of rock-concrete interfaces in underground lined storage systems - Wanniarachchi, Wanniarachchillage Ayal Maneth (2022)
Permeability control on a rock-concrete interface is critical for safe and effective energy storage with concrete lining in host rock. Here we conduct the experimental and numerical studies on mixed granite-concrete samples with uncemented and cemented interfaces to investigate the stress-dependent permeability evolution of a granite-concrete interface. A series of argon permeability experiments on granite, concrete, and hardened cement paste samples are also carried out to isolate the influence of granite-concrete interface on the permeabilities of the mixed samples. A three-dimensional numerical model is used to visualize the distribution of fluid velocity at the uncemented interface and to infer the influence of cement grout on the reduction in flow velocity at the cemented interface. Our results show that cement grouting can reduce not only the interface permeability but also the permeability dependence on effective stress. The permeability reductions of the uncemented and cemented interfaces are comparable under high effective stresses. The numerical results exhibit that the flow velocity becomes inhomogeneous and amplifies in less well-sealed channels when the inlet pressure increases, indicating that fluid leakage can be enhanced in these channels. Our study also suggests that good permeability and cementation controls on a rock-concrete interface can improve the effectiveness of underground energy storage.